Vermiculite as a culture substrate greatly improves the viability of frozen cultures of ectomycorrhizal basidiomycetes. Issue 8 (August 2020) - Sato, Masanori; Inaba, Shigeki; Noguchi, Mariko; Nakagiri, Akira
Abstract: We assessed a new cryopreservation protocol that uses vermiculite as a culture substrate, called the vermiculite protocol (VP), by assessing the viability, recovery time of hyphae after revival, and colony diameter of cryosensitive ectomycorrhizal basidiomycete strains after storage for 2 weeks or 1 year in a vapour-phase liquid nitrogen tank. Twelve difficult-to-preserve strains of nine species ( Amanita citrina, A . pantherina, A . rubescens, A . spissa, Kobayasia nipponica, Lactarius akahatsu, L . hatsudake, Sarcodon aspratus, and Tricholoma flavovirens ) that did not achieve good revival after cryopreservation with our previous Homolka's perlite protocol and modified perlite protocol (MPP) experiments were used to assess the new methodology. Vermiculite and liquid medium were put into a cryotube and inoculated with an agar plug containing mycelia. The cryotube was cultured for various incubation times. After adequate mycelial growth, a mixture of cryoprotectants (5% dimethyl sulfoxide and 10% trehalose [5D10T] or 5% glycerol and 10% trehalose [5G10T]) was placed into the cryotube. The cryotube was frozen in a freezing container in a –80 °C freezer and then stored in vapour-phase liquid nitrogen. In the recovery test, 10 of 12 strains showed 100% revival after 2 weeks of storage in the 5G10T cryoprotectant, and all 12 strains showed 100% revival after 2 weeks of storage in the 5D10T cryoprotectant. Furthermore, all strains were viable after 1 year of storage in a vapour-phase liquid nitrogen tank. Thus, the VP is applicable to a wide range of ectomycorrhizal basidiomycete cultures, including highly cryosensitive strains. Graphical abstract: Image 1 Highlights: A cryopreservation method using vermiculite as a culture substrate for basidiomycetes. All 12 difficult-to-preserve fungal cultures were viable after 1 year of freezing. A mixture of 5% DMSO and 10% trehalose was the most effective cryoprotectant.